Analysis of 4 Components of The Human Development Index (HDI) of North Sumatra Province: A Case Study of Four Cities - Ziady, Rahmad; Juairiyah, Oktaf; Marbun, Valentinus (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Successful regional development cannot be achieved without strong human development. On the contrary, the human development process will be hampered without sustainable regional development. Thus, human quality is an important key to achieving sustainable development. To see the development of a region can be measured by using the Macro Development Indicator (HDI). HDI has several variables of life expectancy at birth, literacy rate, average length of schooling, and per capita expenditure. The purpose of the study was to analyze the condition of the four HDI components in North Sumatra. This study uses the anova test method (a statistical technique used to compare the average between three or more groups (or treatments) in one analysis), normal distribution (a statistical procedure used to test whether the data you have comes from a normal or Gaussian distribution) in one analysis, and linear regression test (a statistical technique used to analyze the relationship between one or more independent variables (usually referred to as variable X) and dependent variables (usually referred to as variable Y) in the context of a linear regression model). The conclusion of this study is based on the Average of 4 HDI components, the city with the highest HDI, namely Medan City, is inversely proportional to Gunungsitoli City with the lowest HDI value. When viewed from the linear regression test, the life expectancy component is the most influential in 2 cities, namely Padangsidimpuan City and Pematang Siantar, the expected length of schooling in Medan City, per capita income in Gunungsitoli City.